The Enhancing Effects of 10% PBS Washout of Holocene Minerals on HuIFN-αN3 Inducing Capacity of NDV ZG1999HDS or Sendai virus (Cantell Strain) - Bratko Filipič; Lidija Gradišnik; Adriana Pereyra; Gordan Mršić; Marjan Andrašec; Hrvoje Mazija (Life, 2022)
Different strains of Newcastle disease viruses (NDV) or Sendai viruses (SV) are used to induce the production of human leukocyte multi subtype interferon-alpha (HuIFN-αN3). Their inducing capacity can be enhanced in different ways. One includes 10% PBS washout of Holocene minerals (HM). The presented study aims to compare the HuIFN-αN3 inducing capacity of NDV ZG1999HDS or SV (Cantell strain) strain in vitro, and to evaluate the enhancing effect of 10% PBS washouts of HM on both viruses. The NDV strains’ ZG1999HDS interferon inducing capacity (483.23 ± 4.5 pg/mL) was similar to that of the SV (Cantell strain) (584.16 ± 5.9 pg/mL). It was shown that the HuIFN-αN3 inducing capacity of the strain of NDV ZG1999HDS can be strongly enhanced with 10% PBS washout of HM to 3818.21 ± 41.9 pg/mL and 4790.34 ± 33.5 pg/mL with SV (Cantell strain), u. The RP-HPLC analyses of such HuIFN-αN3 induced with the strain of NDV ZG1999HDS show the difference to SV (Cantell strain) induced HuIFN-αN3 in the absence of subtype α14 and the lower level of the subtype α1. The possible ways of such enhancement were also studied and it was postulated that the Fe2+ ions from 10% PBS washouts of HM, while stimulating the reactive oxygen species (ROS) and nitric oxide (NO) formation, activate the transcription factor NF- κB and consequently the production of HuIFN-αN3.